2008
DOI: 10.1111/j.1572-0241.2008.01860.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Spherical Adsorptive Carbon for the Treatment of Intractable Anal Fistulas in Crohn's Disease: A Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: AST-120 is useful for the control of intractable anal fistulas in CD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 15 publications
1
31
1
Order By: Relevance
“…Characteristics of individual RCTs, including the magnitude of the placebo response in each trial, are provided in Table 1. Three trials included only patients with perianal fistulizing disease with fistula closure as the primary endpoint, 17,18,28 three trials recruited patients with fistulizing disease exclusively, but at any location, 20,22,26 again reporting fistula closure as the primary endpoint, and seven trials reported fistula closure as a secondary endpoint within a mixed population of patients with either luminal or fistulizing CD. 16,19,21,[23][24][25]27 Six trials were at low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of individual RCTs, including the magnitude of the placebo response in each trial, are provided in Table 1. Three trials included only patients with perianal fistulizing disease with fistula closure as the primary endpoint, 17,18,28 three trials recruited patients with fistulizing disease exclusively, but at any location, 20,22,26 again reporting fistula closure as the primary endpoint, and seven trials reported fistula closure as a secondary endpoint within a mixed population of patients with either luminal or fistulizing CD. 16,19,21,[23][24][25]27 Six trials were at low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 44 RCTs, 31 were excluded for the reasons listed, leaving 13 eligible trials, [16][17][18][19][20][21][22][23][24][25][26][27][28] containing 579 individuals with fistulizing CD who were randomized to receive placebo. Agreement between reviewers for assessment of trial eligibility was good (kappa statistic = 0.90).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty-two patients were randomized, 57 of whom received AST-120 (n = 27) or placebo (n = 30) [37] . The improvement rate in the AST-120 group (37.0%) was significantly higher than that in the placebo group (10.0%; p = 0.025).…”
Section: Other Medical Therapiesmentioning
confidence: 99%
“…A summary of different studies on medical therapy options in fistulizing CD is shown in table 1 [10,12,13,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . Vavricka …”
Section: Medical Therapiesmentioning
confidence: 99%